ХОДЖКИН ЛИМФОМАСИДАГИ МОРФОЛОГИК ЎЗГАРИШЛАРНИ ИММУНОГИСТОКИМЁВИЙ ХАРАКТЕРИСТИКАСИ (РИО ва РИАТМ СУРХОНДАРЁ ФИЛИАЛИДА 2020-2023 ЙИЛЛАРИДА) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article evaluates the histological characteristics of patients living in the Surkhandarya region, diagnosed with Hodgkin lymphoma, who were treated at the Republican specialized oncological and radiological scientific and practical medical center in the Surkhandarya branch and were under the supervision of the dispensary during 2020-2023, based on the data obtained from our retrospective study of the results of biopsy reports. Resections were taken from tissues obtained by surgery and biopsy. The materials were processed in accordance with the instructions for the Unification of Histological Examination Methods Thermo Fisher Scientific histoprocessor, and the results of the analysis obtained during the microscopic study of histological and immunohistochemical changes in the histological forms of Hodgkin lymphoma are described.